Seroprevalence of Babesia microti in Individuals with Lyme Disease - Curcio, Sabino R; Tria, Laurel P; Gucwa, Azad L (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2016)
Babesiosis is an emerging tick-borne disease (TBD) caused by Babesia microti, an intracellular parasite of red blood cells. Currently, it is the highest ranked pathogen transmitted by blood transfusion. Most healthy individuals infected with B. microti are asymptomatic, but may be at risk for chronic infection. Similar to Lyme disease transmitted by Borrelia burgdorferi, B. microti is spread by Ixodes scapularis ticks. The rate of coinfection with these TBDs in humans is unclear as most studies have focused their prevalence in ticks or rodent reservoirs. In this study, we aimed to determine the seroprevalence of B. microti infection in individuals who tested positive for Lyme disease. Serum samples obtained from 130 subjects in New York were tested by immunofluorescence assay (IFA) for the presence of IgM and IgG antibodies against B. microti. Overall, 26.9% of the serum samples tested were positive for IgM and IgG antibodies against B. microti, suggesting exposure to TBD. Individuals who tested positive for Lyme disease as determined by two-tiered serological testing and the presence of both IgM and IgG antibodies directed against B. burgdorferi, were significantly increased for antibodies directed against B. microti (28.6%; p < 0.05), suggesting the possibility of coinfection with both TBDs. In contrast, the Lyme disease-negative control group had only 6.7% of samples seropositive for B. microti. These findings suggest the need for more extensive studies investigating infection rates with multiple TBDs in areas where they are endemic and further support for the need to implement an FDA-approved screening test for blood products to help prevent transfusion-transmitted babesiosis.